Academic support as a ‘third space’: a team’s reflection on post-pandemic practice - Jon Baldwin; Bonita Charles; Emma Davenport; John Keefe; Debora Minà (Journal of Learning Development in Higher Education)
This paper describes and reflects upon the re-organisation of academic support across a department of architecture, art and design within a British post-92 university drawing on the concept of ‘third space’ in relation to student success. Both the department and the institution are committed to social justice, widening participation and academic success. With the introduction of online support during the pandemic and a new team of colleagues, an opportunity arose to revise how academic support was delivered to undergraduate students. For this team, which includes academic mentors and an academic manager, the COVID-19 pandemic brought challenges that impacted our historical delivery of academic support, requiring us to redefine our service to students and colleagues in the light of student success and inspired by the concept of the ‘third space’. This paper reflects upon the changes we made, as a case study, with reference to quantitative data, students’ feedback and Whitchurch’s (2009) framework of knowledges, legitimacies and relationships for blended professionals.